Theoretical basis and technical conception of backfill carbon fixation in coal mine - Lang LIU; Zhiyu FANG; Shuangming WANG; Guobin GAO; Bo ZHANG; Yujiao ZHAO; Mengbo ZHU; Zhichao LIU; Jingyu WANG; Jing ZHOU; Yan LI; Mei WANG; et al. (Meitan kexue jishu, 2024)
Under the national “dual carbon” goal, how to reduce the carbon emissions of the coal industry and achieve carbon storage has become an urgent problem to be solved. The coal industry is the producer of high carbon fossil energy and the main carbon emission source provider. In the process of production and consumption, the accumulation of bulk solid waste, the formation of large goaf and a large amount of CO2 emissions are the bottlenecks that restrict the sustainable development and utilization and the green and healthy development of the coal industry. In order to solve the problem of carbon dioxide storage and mine waste consumption, the bulk solid waste disposal, high-value solid waste utilization, CO2 storage and goaf utilization were organically combined, the concept of carbon dioxide backfill was put forward, and three types of dioxide backfill were defined from the perspective of carbon sink capacity assessment. ① The basic theories involved in the transportation process of CO2 filling slurry and mineralization reaction process are analyzed. The mathematical equations for each process and calculation formulas for carbon sequestration amount are provided. The influence of factors such as temperature and humidity on the mineralization reaction mechanism, carbon sequestration amount, and strength of the backfill body are pointed out. ② The carbonation technological approaches, CO2 sequestration capacity of major alkaline industrial solid wastes and enhancing measures of CO2 mineralization are summarized. On this premise, two types of CO2 backfill materials preparation technique based on direct carbonationand or indirect carbonationand are presented, which can fulfill the criterion of mine backfill in fluidity, solidification characteristics and strength. ③ To solve the problem of decomposed CO2 escaping during CO2 backfill, two technical paths of strip roadway paste backfilling and intermittent backfilling behind packed hydraulic support have been proposed. The former sequesters decomposed CO2 by constructing backfilling bodies with multiple through holes in the weak backfilling strip, while the latter uses packed hydraulic support and chain self-filling baffling to construct backfilling strips in longwall goaf to control roof caving and form a CO2 physicochemical storage space. ④ In order to evaluate the carbon balance effect of CO2 backfill, the calculation boundary of carbon footprint and carbon sequestration in CO2 backfill was defined according to the life cycle method, including the stages of raw material mining, transportation, processing, injection, solidification, etc. Then, the carbon footprint and carbon sequestration in the CO2 backfill process were sorted out, and factors such as the source, dosage, loss, and conversion of CO2 were considered. Next, the calculation methods of carbon footprint and carbon sequestration in the processes of raw material transportation, filling slurry preparation, underground injection and filling were given. The research results are expected to reduce the energy consumption and cost of CO2 storage, and have far-reaching significance for green coal mining and sustainable development and utilization.